Self-service technology in aviation : the case study of Thailand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Aviation at Massey University, Manawatu Campus, New Zealand - Wongyai, Phutawan Ho (Massey University, 2026)
As a major tourist destination, Thailand’s economy relies heavily on air transport. The post- pandemic air travel sector still faces operational challenges, including airport congestion and staff shortages. These issues have accelerated the adoption of self-service technology (SST) to tackle these challenges and improve passenger experience. This thesis examines SST within aviation, passenger adoption, and its effects on ground employees, using Thailand as a case study. Chapter 1 reviews the literature on SST in aviation, identifying potential research gaps. This chapter maps the research landscape, identifying a considerable lack of studies on the new biometric check-in kiosks, and highlighting the limited research concerning the effects of SST implementation on ground employees. Chapter 2 explores how passengers adopt biometric check-in kiosks by combining the Technology Acceptance Model with the Theory of Planned Behaviour, broadening these models to incorporate less researched factors in aviation context, such as perceived risk, trust, and privacy issues. The results highlight the critical role of perceived trust and privacy concerns in influencing attitudes toward the use of this technology. Chapter 3 investigates the perceived threat of job automation from SST on airlines and airports ground employees. The findings illustrate the influence of this threat on, job insecurity, job satisfaction, and organisational commitment on turnover intentions. This thesis contributes to the aviation literature by synthesising insights from both passenger and employee perspectives. It also offers managerial implications for optimising future SST implementation strategies. Specifically, it recommends that aviation stakeholders must facilitate biometric adoption by actively communicating the technology’s benefits and data privacy measures to reshape passenger attitudes and build trust. Simultaneously, mitigate ground staff job insecurity through targeted upskilling and role integration to ensure workforce retention.
Keywords: self-service technology; aviation; passengers; technology acceptance; 350901 Air transportation and freight services